Hypervalent Iodine Chemistry as a Platform for Aerobic Oxidation Catalysis - Maity, Asim; Powers, David C. (Synlett, 2019)
Here, we highlight the recent development of aerobic oxidation catalysis via hypervalent I(III) and I(V) intermediates. The described chemistry intercepts reactive intermediates generated during aldehyde autoxidation to accomplish the oxidation of aryl iodides. The aerobically generated hypervalent iodine intermediates are utilized to couple an array of substrate functionalization chemistry to the reduction of O2.1 Introduction2 Chemistry of Aerobically Generated I(III) Intermediates3 Chemistry of Aerobically Generated I(V) Intermediates4 Conclusions
Keywords: aerobic oxidation; hypervalent iodine; organocatalysis; sustainable synthesis